Oxygen-mediated heterogeneity of apo-low-density lipoprotein. - Schuh, J (1978)
Mild oxidation of human serum low-density lipoprotein (LDL) converts the apoprotein from a nearly homogeneous component of high apparent molecular weight to a mixture of apparently lower molecular weight polypeptide components, as characterized by sodium dodecyl sulfate/polyacrylamide gel electrophoresis. This protein alteration, which correlates temporally with increases in the formation of lipid oxidation products and in the fluorescence of the apoprotein, is markedly reduced when oxygen is excluded or when EDTA or the free-radical-scavenging antioxidants, butylated hydroxytoluene or propyl gallate, are added. The conversion thus appears to be due to a reaction between the protein moiety and auto-oxidizing lipid. The presence of the antibacterial agent sodium azide markedly accelerates the oxidation, suggesting that it should only be used with caution in lipid-containing solutions.